AN ANALYSIS OF FIGURATIVE LANGUAGE IN LORDE’S SELECTED SONG AND ITS CONNOTATIVE MEANING - Roobby Hamdanur (ELATICS JOURNAL, 2025)
This study investigated the figurative language in Lorde’s selected song entitled “Royals” and its connotative meaning. This study was descriptive qualitative research. The source of the data was Lorde selected song entitled “Royals”. The data were word, phrase, clause, and sentence in the song expressing figurative language. The finding indicated that there were 16 figurative languages found in “Royals” lyric. They were simile, personification, metaphor, symbolism, metonymy, hyperbole, understatement, and irony. The most frequent figurative language found in “Royals” lyric was symbolism since it symbolized the materialism in American society. The connotative meaning of the whole figurative language is negative because it shows the rejection of materialism in American society.